2018
DOI: 10.1039/c8dt00016f
|View full text |Cite
|
Sign up to set email alerts
|

1D–2D hybrids as efficient optoelectronic materials: a study on graphitic carbon nitride nanosheets wrapped with zinc oxide rods

Abstract: Zinc oxide (ZnO) nanorods (NRs) wrapped with graphitic carbon nitride (GCN) nanosheet (NS) hybrids have been synthesized by a simple chemical process. The as-prepared samples are characterized by X-ray diffraction, field emission scanning electron microscopy, high resolution transmission electron microscopy, Fourier transformed infrared spectroscopy, UV-Vis spectroscopy and photoluminescence spectroscopy. The images obtained from the transmission electron microscopic study and the existence of C-N stretching m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…87–1526), whereas wurtzite hexagonal structures (JCPDS no 36–1451) confirms the crystalline nature of prepared nanocomposite. 36 , 46 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…87–1526), whereas wurtzite hexagonal structures (JCPDS no 36–1451) confirms the crystalline nature of prepared nanocomposite. 36 , 46 …”
Section: Resultsmentioning
confidence: 99%
“…Figure shows the XRD peaks of g-C 3 N 4 /ZnO observed at 2θ values of 12.3, 27.5, 31.75, 34.42, 35.95, 47.42, 56.54, 62.81, 66.86, 67.81, and 69.06° corresponding to (100), (002), (100), (002), (101), (102), (110), (103), (200), (112), and (201), confirming the crystalline structure of g-C 3 N 4 /ZnO that well-matched and identified with heptazine units (JCPDS no. 87–1526), whereas wurtzite hexagonal structures (JCPDS no 36–1451) confirms the crystalline nature of prepared nanocomposite. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed similar results, revealing that compared to individual g‐CN and ZnO, the hybrid featured higher conductivity due to charge transfer and exhibited enhanced violet‐blue emission after optical excitation. [ 118 ] Charge transfer was also responsible for the increase in the dark current and photocurrent observed for g‐CN/ZnO hybrids.…”
Section: Optoelectronic Applicationsmentioning
confidence: 99%
“…Such a nanocomposite can solve the individual drawbacks of ZnO and C 3 N 4 and acts as a potential photocatalyst for the effective degradation of rhodamine B (RhB). Based on the dimensionality of the nanostructures of ZnO and C 3 N 4 , various research groups presented their results in the literature on 0D/2D [32][33][34][35][36], 1D/0D [37], 1D/2D [38][39][40][41][42][43], 2D/0D [44], 2D/2D [45], and 3D/2D [31] heterojunction composites (where 0D, 1D, 2D, and 3D are zero-, one-, two-, and three-dimensional composites) involving ZnO and C 3 N 4 , respectively. Sharma et al designed a ZnO/g-C 3 N 4 photocatalyst for the removal of methylene blue (MB).…”
Section: Introductionmentioning
confidence: 99%